Evaluation of porous asphalt mixtures stabilized by human scalp hair - A.M. Youssef; E.A. Fahmy (Case Studies in Construction Materials, 2023)
Porous asphalt (PA) is an open-graded hot mixed asphalt that presents improved surface drainage during rainfall, improving road safety in wet weather and preventing rainfall water from receding in closed areas. The main challenge facing PA paving is binder draindown during mix transportation and placement due to the confluence of low fillers cases, open-graded aggregate gradation, and high asphalt contents. Mineral fibers such as slag wool (SW), despite their negative effects on human health and the environment, have been used as stabilizers in PA mixtures to increase binder retention and avoid stability reduction. This study evaluates using human scalp hair (HSH) as an alternative stabilizing fiber to SW in PA mixtures. Using HSH in PA mixtures is a sustainable waste recycling method and an economical solution to enhance the binder retention and stability of PA mixtures. The performance of the PA mixtures that stabilized with SW (control) and HSH was compared with National Asphalt Pavement Association (NAPA) requirements. The fiber length of 1–5 mm was maintained for SW and HSH. The PA standard gradation suggested by NAPA was used to form the stone matrix of the investigated PA mixtures. The Marshall design method was used to obtain the optimum asphalt and stabilizer contents. The performance evaluation tests were performed on SW and HSH mixtures, including loss of stability, moisture sensitivity, draindown, cantabro abrasion and rutting depth. Based on the results of the performance evaluation tests, the PA mixtures stabilized by HSH show a convergent performance compared with those stabilized by SW. The findings indicated that HSH can be considered an adequate stabilizer for PA mixtures instead of SW fibers.